Cardiac Arrest as an Uncommon Manifestation of Late Type A Aortic Dissection Associated with Transcatheter Aortic Valve Replacement - Naar, Jan; Vondráková, Dagmar; Kruger, Andreas; Janotka, Marek; Zemanova, Iva; Syrucek, Martin; Neuzil, Petr; Ostadal, Petr (Journal of clinical medicine, 2023)
Transcatheter aortic valve replacement (TAVR) is a minimally invasive therapeutic procedure with a consistent, linear increase in the number of implantations worldwide. Recently, TAVR has been rapidly expanding into lower-risk populations. Sporadic cases of late prosthesis-related Stanford type A dissection have been documented in self-expanding, as well as balloon-expandable TAVR valves, manifested primarily as acute aortic syndrome. We present the case of a 76-year-old male, who experienced refractory in-hospital cardiac arrest with non-shockable rhythm due to the obstruction of coronary flow caused by aortic dissection type A, with entry directly adjacent to the aortic prosthesis according to autopsy. The patient died despite the engagement of extracorporeal cardiopulmonary resuscitation. Aortic dissection developed one year after a transfemoral TAVR procedure using an Edwards SAPIEN 3 29 mm self-expanding valve. TAVR-associated late aortic dissection type A represents a rare, life-threatening condition with various clinical manifestations. The risk factors have not been well described and the differential diagnosis may be challenging. As the number of TAVR recipients and their life expectancy is increasing, we may face this complication more often in future.